(untitled) (Journal of Medical & Health Sciences Review, 2025)
Coronary artery disease (also known as CAD) is one of the most significant health issues in the contemporary world and is one of the leading causes of premature mortality. Screening for CAD is thus important in limiting the incidence of such complications as myocardial infarction, heart failure, and sudden cardiac death. ECG is still among the most benign and relatively inexpensive diagnostic procedures. Therefore, the application of non-specific ECG alterations in confirming CAD is still questionable. This cross-sectional study was carried out to determine the relationship between nonspecific ECG changes such as QTc interval prolong, wide QRS duration, and QRS axis deviation and CAD in patients admitted to a tertiary hospital. Therefore 387 chest pain patients who had both ECG and coronary angiography or CT coronary angiography were available for analysis. It was found that high QT intervals and QRS axis deviations were favourable with CAD; specifically in multivessel disease. The findings of this study will imply that ECG alterations like QT interval prolongation and QRS axis deviation may be used as an initial indicator of CAD, particularly in situations the more enhanced diagnostic technologies are not available. Future studies should also be conducted to compare the efficiency of ECG with other diagnostic tools for more effective detection of CAD.